2018
DOI: 10.1142/s0218126618501384
|View full text |Cite
|
Sign up to set email alerts
|

A Side-Channel Analysis for Hardware Trojan Detection Based on Path Delay Measurement

Abstract: Hardware Trojan Horses (HTHs) are malicious modifications inserted in Integrated Circuit during fabrication steps. The HTHs are very small and can cause damages in circuit function. They cannot be detected by conventional testing methods. Due to dangerous effects of them, Hardware Trojan Detection has become a major concern in hardware security. In this paper, a new HTH detection method is presented based on side-channel analysis that uses path delay measurement. In this method, we find and observe the paths t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The main advantage of the SCA approach is its ability to detect HTs even when HTs are not activated. The larger the HT, the more effective this method is and the simpler testing process [4][5]. Currently, SCA is considered among the most efficient techniques for HT detection [5].…”
Section: Existing Techniques For Hardware Trojan Detectionmentioning
confidence: 99%
“…The main advantage of the SCA approach is its ability to detect HTs even when HTs are not activated. The larger the HT, the more effective this method is and the simpler testing process [4][5]. Currently, SCA is considered among the most efficient techniques for HT detection [5].…”
Section: Existing Techniques For Hardware Trojan Detectionmentioning
confidence: 99%
“…Further, conclusive testing by performing a side channel analysis on the true positive trojan boards can improve the coverage of detecting hardware trojans. (Amelian and Borujeni 2018). This will help reduce the redundancy of testing all the boards for hardware trojans.…”
Section: Improvement In Recognition Of Hardware Trojansmentioning
confidence: 99%
“…Amelian et al [ 130 ] suggested a new kind of side-channel signal detection technique that doesn’t modify the circuit design and the hardware overhead. Moreover, the common side-channel signal detection techniques in VLSI have an alternative path to test.…”
Section: Hardware Trojans Protectionmentioning
confidence: 99%